2018
DOI: 10.1002/jso.25075
|View full text |Cite
|
Sign up to set email alerts
|

Oral rehabilitation of the cancer patient: A formidable challenge

Abstract: Rehabilitation of oral functions following surgery on the jaws is a goal that is often difficult to achieve. Removable dentures supported by remaining teeth or gum are often unstable and seldom satisfactory. On the other hand, endosseous (dental) implants offer a mechanism to provide stability to the dentures. This review, discusses factors related to the tumor, patient, treatment, and physicians which impact upon the feasibility and success of dental implants in patients with oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 39 publications
0
68
0
11
Order By: Relevance
“…The survival of implants in irradiated HNC patients have been investigated and may be a successful part of the oral rehabilitation . However, the general opinion is still not to perform surgery on irradiated patients including insertion of implants because of the risk of developing osteoradionecrosis but opinions on this topic are divergent in the literature …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The survival of implants in irradiated HNC patients have been investigated and may be a successful part of the oral rehabilitation . However, the general opinion is still not to perform surgery on irradiated patients including insertion of implants because of the risk of developing osteoradionecrosis but opinions on this topic are divergent in the literature …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that use of implant-supported prostheses may improve the outcome of oral rehabilitation in HNC patients. 12 By using implants, the prosthesis could be stabilised and lack of saliva and poor retention may not be a great obstacle. This could in turn improve the function of the prosthesis and thus the OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors and systematic reviews have already shown good outcomes of implant surgery and dental implant‐supported prosthetics in patients with HNC. High implant survival rates and restoration of a good quality of life have been reported . After facial RT, it is now commonly thought that oral implant surgery can be performed at the irradiated sites .…”
Section: Introductionmentioning
confidence: 99%